Potential Applications of Gliclazide in Treating Type 1 Diabetes Mellitus: Formulation with Bile Acids and Probiotics - Mikov, M.; Ðanic, M.; Pavlovic, N.; Stanimirov, B.; Golocorbin-Kon, S.; Stankov, K.; Al-Salami, Hani (Springer France, 2017)
© 2017 Springer International Publishing AG A major advancement in therapy of type 1 diabetes mellitus (T1DM) is the discovery of new treatment which avoids and even replaces the absolute requirement for injected insulin. The need for multiple drug therapy of comorbidities associated with T1DM increases demand for developing novel therapeutic alternatives with new mechanisms of actions. Compared to other sulphonylurea drugs used in the treatment of type 2 diabetes mellitus, gliclazide exhibits a pleiotropic action outside pancreatic ß cells, the so-called extrapancreatic effects, such as antiinflammatory and cellular protective effects, which might be beneficial in the treatment of T1DM. Results from in vivo experiments confirmed the positive effects of gliclazide in T1DM that are even more pronounced when combined with other hypoglycaemic agents such as probiotics and bile acids. Even though the exact mechanism of interaction at the molecular level is still unknown, there is a clear synergistic effect between gliclazide, bile acids and probiotics illustrated by the reduction of blood glucose levels and improvement of diabetic complications. Therefore, the manipulation of bile acid pool and intestinal microbiota composition in combination with old drug gliclazide could be a novel therapeutic approach for patients with T1DM.